Impaired hippocampal-dependent learning and functional abnormalities in the hippocampus in mice lacking serotonin(1A) receptors - Sarnyai, Zoltán (The National Academy of Sciences, 2000)
The hippocampus is a major limbic target of the brainstem serotonergic neurons that modulate fear, anxiety, and learning through postsynaptic serotonin(1A) receptors (5-HT(1A) receptors). Because chronic stress selectively down-regulates the 5-HT(1A) receptors in the hippocampus, we hypothesized that mice lacking these receptors may exhibit abnormalities reminiscent of symptoms of stress-related psychiatric disorders. In particular, a hippocampal deficit in the 5-HT(1A) receptor could contribute to the cognitive abnormalities often seen in these disorders. To test whether a deficit in 5-HT(1A) receptors impairs hippocampus-related functions, we studied hippocampal-dependent learning and memory, synaptic plasticity in the hippocampus, and limbic neuronal excitability in 5-HT(1A)-knockout (KO) mice. 5-HT(1A)-KO animals showed a deficit in hippocampal-dependent learning and memory tests, such as the hidden platform (spatial) version of the Morris water maze and the delayed version of the Y maze. The performance of KO mice was not impaired in nonhippocampal memory tasks such as the visible platform (nonspatial) version of the Morris water maze, the immediate version of the Y maze, and the spontaneous-alternation test of working memory. Furthermore, paired-pulse facilitation in the dentate gyrus of the hippocampus was impaired in 5-HT(1A)-KO mice. Finally, 5-HT(1A)-KO mice, as compared with wild-type animals, displayed higher limbic excitability manifested as lower seizure threshold and higher lethality in response to kainic acid administration. These results demonstrate that 5-HT(1A) receptors are required for maintaining normal hippocampal functions and implicate a role for the 5-HT(1A) receptor in hippocampal-related symptoms, such as cognitive disturbances, in stress-related disorders.